Managing crime through migration law in Australia and the United States: a comparative analysis - Khanh Hoang; Sudrishti Reich (Comparative Migration Studies, 2017)
Abstract This article examines the intertwining of migration law and criminal law — termed ‘crimmigration’ by scholars — in Australia and the United States of America, and its implications for non-citizens who engage in criminal conduct. Our comparison of the two systems demonstrates that the laws and policies in both jurisdictions are similar to a significant degree. Both have strong exclusionary policies characterised by sweeping visa cancellation/removal powers, a heavy focus on enforcement, and limited review rights. In Australia, legislative amendments in 2014 have given the executive greater powers to cancel visas and remove non-citizens on character grounds as a means of ensuring national security and public safety. This has coincided with a new law enforcement body created within the Australian Department of Immigration. These changes reflect a repurposing of migration law as a tool for managing criminal threats based on the concept of ‘risk management’. Drawing on the experience of the United States — where such a ‘risk management’ approach is entrenched — we query the utility of this shift and highlight the potential pitfalls of pursuing such a policy for Australia.